"I Lost Me Visits": A Critical Examination of Prison Drug Policy and Its Effects on Connection to Family for Incarcerated Young Men With Histories of Injecting Drug Use. (September 2018) - Walker, Shelley; Lancaster, Kari; Stoové, Mark; Higgs, Peter; Wilson, Mandy
Utilizing Bacchi's poststructuralist approach, "What's the problem represented to be?, " we critically examine how the "problem" of drug use in prison is represented within a key initiative—the Identified Drug User program (IDUP)—of prison drug policy in one Australian jurisdiction. We use two data sources for our analysis: interview transcripts of recently incarcerated young men (aged 19–24) with histories of injecting drug use and selected prison drug policy and program documents. We examine how the "problem" of drug use in prison is problematized within the IDUP and question commonly accepted ways of thinking that underpin the program. We explore the discursive and subjectification effects of problem representations which produce young men as "rational" and "choosing" and, at the same time, as "untrustworthy" and "deserving of punishment." We highlight how these effects have consequences for young men's connections to family while incarcerated which can work against the very issues the IDUP is trying to address. We make two claims in particular: that the IDUP produces harmful effects for young men and their families and that the harmful effects produced are, paradoxically, those the IDUP aims to avoid. Our analysis offers insights into how drug use in prison could be thought about differently, including suggestions that might reduce at least some of its adverse effects.